Identification of a gene encoding GMP synthetase from a Neurospora crassa cDNA library by bacterial complementation - J A Smiley; D K Asch (Fungal Genetics Reports, 2000)
We report the isolation and identification of a gene encoding GMP synthetase from a Neurospora crassa cDNA library. Phage infection of the purine-requiring Escherichia coli strain SØ3834 using the NO3- induced cDNA phage library from the Fungal Genetics Stock Center resulted in colonies able to grow on minimal media with no added purine source. A plasmid, termed pGMPS1, was isolated from one of these colonies and shown to reproducibly support growth of strain SØ3834 in the absence of purines in the media. Identification of this gene as one encoding GMP synthetase is confirmed by DNA sequencing and comparison to the known guaA gene from yeast.